Hedysarum vuralii (Fabaceae), a new species from Turkey - Ertuğrul, Tuğba; Yildiz, Bayram; Günay Öztürk, Meryem; Fi̇şne, A.; Bağ, Ecem; Aytaç, Zeki̇ (Phytotaxa, 2024)
Hedysarum vuralii, a new species in the tribe Hedysareae (Fabaceae), is described and illustrated. It belongs to Hedysarum section Multicaulia, collected from Ankara province in Turkey. H. vuralii is closely related to H. dededaghense but differs in densely adpressed white sericeous stem indumentum (versus spreading pilose); 7–10 paired, narrower, and glabrous above leaflets (5–16 ×1–3 mm, versus 7–8 paired, oblong-elliptic, 5–20 × 2–5 mm, spreading hairy on both surface); longer bracteoles (5–6 mm long, versus 3–4 mm); calyx teeth at least twice as long as tube (versus as long as tube); corolla greenish yellow, violet spotted at tips (versus purple); shorter standard (15–16 mm long, versus 19 mm); pods 12 × 4 mm, 2 (–3)-jointed (versus 14 × 5–6 mm, 1–2 jointed); joints 4–6 × 2–4 mm, pubescent with echinate in the center (versus c. 6 ×6, pubescent with setae). Taxonomic descriptions, images, the identification key, phenology, palynology, and the IUCN threat category of the new species were presented. Moreover, the geographical distribution of H. vuralii and H. dededaghense were mapped.